Organizational identity as an anchor for adaptation: an emerging market perspective - Hatum, Andrés (2012)
There is little doubt that organizational identity – that which is central, distinctive, and enduring about an organization – mediates in adaptive processes. Exactly how this mediation takes place, and whether it is favorable or unfavorable to adaptation, must still be fully established. The purpose of this paper is to add to the literature on identity and adaptation by exploring the relationship between these two constructs in family firms operating in an emerging economy. Based on measures of strength of identity, the authors examine how identity affects the adaptive processes of issue identification, strategic impulse definition, and implementation, where the authors look at pace of adjustment. Longitudinal and comparative case studies were conducted of polar types presenting two pairs of organizations in two separate industries. These organizations faced the challenge of founder succession and a radical shift in macroeconomic conditions over a period of three decades. Through these four cases the authors hope to provide clear pattern recognition of strength of identity and adaptation – and of the relationship between these two constructs – in the face of severe internal and external shocks. The approach seems adequate in the larger context of inductive theory development and particularly suitable to the exploration of theoretical constructs, as it allows the researcher to unravel the underlying dynamics of path dependencies and/or evolutionary processes. It is found that strong-identity organizations are able to foresee relevant changes in their industries, define adequate strategic responses, and implement them in an evolutionary (i.e. smooth) manner. Conversely, loose-identity organizations misread industry trends, incur strategic paralysis, and must eventually enforce revolutionary (i.e. violent) changes in order to ensure survival. The paper addresses a critical issue for the advancement of organizational theory: the relationship between organizational identity and adaptation in emerging economies. In addition, it has important practical implications for managers doing business in turbulent environments. It makes a sound theoretical contribution and has important managerial implications.